The Piroplasmida Babesia, Cytauxzoon, and Theileria in farm and companion animals : species compilation, molecular phylogeny, and evolutionary insights - Schnittger, Leonhard (2022)
The order Piroplasmida, including the genera Babesia, Cytauxzoon, and Theileria is often referred to as piroplasmids and comprises of dixenous hemoprotozoans transmitted by ticks to a mammalian or avian host. Although piroplasmid infections are usually asymptomatic in wild animals, in domestic animals, they cause serious or life-threatening consequences resulting in fatalities. Piroplasmids are particularly notorious for the enormous economic loss they cause worldwide in livestock production, the restrictions they pose on horse trade, and the negative health impact they have on dogs and cats. Furthermore, an increasing number of reported human babesiosis cases are of growing concern. Considerable international research and epidemiological studies are done to identify existing parasite species, reveal their phylogenetic relationships, and develop improved or new drugs and vaccines to mitigate their impact. In this review, we present a compilation of all piroplasmid species, isolates, and species complexes that infect domestic mammals and which have been well defined by molecular phylogenetic markers. Altogether, 57 taxonomic piroplasmid entities were compiled, comprising of 43 piroplasmid species, 12 well-defined isolates awaiting formal species description, and two species complexes that possibly mask additional species. The extrapolation of the finding of at least 57 piroplasmid species in only six domestic mammalian groups (cattle, sheep, goat, horse, dog, and cat) allows us to predict that a substantially higher number of piroplasmid parasites than vertebrate host species exist. Accordingly, the infection of a vertebrate host species by multiple piroplasmid species from the same and/or different phylogenetic lineages is commonly observed. Molecular phylogeny using 18S rRNA genes of piroplasmids infecting domestic mammals results in the formation of six clades, which emerge due to an anthropocentric research scope, but not due to a possibly assumed biological priority position. Scrutinizing the topology of inferred trees reveals stunning insights into some evolutionary patterns exhibited by this intriguing group of parasites. Contrary to expectations, diversification of parasite species appears to be dominated by host-parasite cospeciation (Fahrenholz’s rule), and, except for piroplasmids that segregate into Clade VI, host switching is rarely observed. When only domestic mammalian hosts are taken into account, Babesia sensu lato (s.l.) parasites of Clades I and II infect only dogs and cats, respectively, Cytauxzoon spp. placed into Clade III only infect cats, Theileria placed into Clade IV exclusively infect horses, wheras Theileria sensu stricto (s.s.) of Clade V infects only cattle and small ruminants. In contrast, Babesia s.s. parasites of Clade VI infect all farm and companion animal species. We outline how the unique ability of transovarial transmission of Babesia s.s. piroplasmids of Clade VI facilitates species diversification by host switching to other host vertebrate species. Finally, a deterioration of sequence fidelity in databases is observed which will likely lead to an increased risk of artifactual research in this area. Possible measures to reverse and/or avoid this threat are discussed.